Membebaskan Ilmu Sosial dari Keterperangkapan Ganda - Gumilar Rusliwa Somantri (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2005)
Social Science in Indonesia facing the challenge to he more authonomous. The science and scientist have to involve themself in a productive dialog with the Western tradition and at the same time, play a significant role in answering the problems related to the ongoing social change. It seems, it is a must for social science to escape itself from the multiple traps of assumption, theory, methodology and orientation, in order to answer successfully the challenge of dynamics of humanity and civilization.